Antimicrobial Potential and Phytochemical Investigation of Fixed Oil of Plant Chenopodium ambrosioides Linn. - Nisar, Muhammad; Shah, Hameed; Khan, Inamullah; Rehman, Fazal-ur-; Shoaib Khan, Muhammad; Khan Marwat, Sarfaraz; Rasul Niazi, Zahid; Ullah, Aziz (Asian Journal of Chemistry, 2012)
Chenopodium ambrosioides is widely used in the traditional medicine system, due to anthelmintic, anticancerous ant antiparasitic activities in Asia, America and Africa. To investigate the fixed oil composition of the plant and evaluate its biological activities, we have selected this medicinal plant for further studies. Twenty four different methyl esters were found in the oil having palmitic acid, linoleic acid, oleic acid, stearic acid, linolenic acid, behenic acid, myristic acid and pentadecanoic acid. The oil also had antimicrobial activity against selected strains of Gram-positive bacteria, Gram-negative bacteria and some fungi species. The results confirm the biological activity of the fixed oil and proved its importance as natural medicinal source.